Three-Dimensional Models as a New Frontier for Studying the Role of Proteoglycans in the Normal and Malignant Breast Microenvironment - Clegg, Julien; Koch, Maria K.; Thompson, Erik W.; Haupt, Larisa M.; Kalita-de Croft, Priyakshi; Bray, Laura J. (Frontiers in Cell and Developmental Biology, 2020)
The extracellular matrix (ECM) provides cues to direct mammogenesis, tumourigenesis and metastatic processes. Over the past several decades, two-dimensional (2D) culture models have been invaluable in furthering our understanding of the tumour microenvironment (TME) however, they still do not accurately emulate the associated biological complexities. In contrast, three-dimensional (3D) culture models provide a more physiologically relevant platform to study relevant physicochemical signals, stromal-epithelial cell interactions, vascular and immune components, and cell-ECM interactions in the human breast microenvironment. A common thread that may weave these multiple interactions are the proteoglycans (PGs), a prominent family of molecules in breast tissue. This review will discuss how these PGs contribute to the breast cancer TME and provide a summary of the traditional and emerging technologies that have been utilised to better understand the role of PGs during malignant transformation. Furthermore, this review will emphasise the differences that PGs exhibit between normal tissues and tumour ECM, providing a rationale for the investigation of underexplored roles of PGs in breast cancer progression using state-of-the-art 3D culture models.